Characterization of the defect density states in MoOx for c-Si solar cell applications. (November 2021) - Scirè, D.; Macaluso, R.; Mosca, M.; Mirabella, S.; Gulino, A.; Isabella, O.; Zeman, M.; Crupi, I.
Highlights: Defects in the selective contacts affect the transport mechanism in solar cells. The density of states (DOS) of the transition metal oxides is unexplored. The deconvolution of the absorption spectra is a viable method for extrapolating the DOS. DOS distributions and small polaron parameters extrapolated for thin films of MoO3 . Abstract: Thin layers of MoOx have been deposited by thermal evaporation followed by post-deposition annealing. The density of states distributions of the MoOx films were extracted deconvoluting the absorption spectra, measured by a photothermal deflection spectroscopy setup, including the small polaron contribution. Results revealed a sub-band defect distribution centered 1.1 eV below the conduction band; the amplitude of this distribution was found to increase with post-deposition annealing temperature and film thickness.